A Control Method to Balance the Efficiency and Reliability of a Time-Delayed Pump-Valve System. (26th September 2016) - Lai, Zhounian; Wu, Peng; Yang, Shuai; Wu, Dazhuan
Abstract : The efficiency and reliability of pumps are highly related to their operation conditions. The concept of the optimization pump operation conditions is to adjust the operation point of the pump to obtain higher reliability at the cost of lower system efficiency using a joint regulation of valve and frequency convertor. This paper realizes the control of the fluid conveying system based on the optimization results. The system is a nonlinear Multi-Input Multioutput (MIMO) system with time delays. In this paper, the time delays are separated from the system. The delay-free system is linearized using input-output linearization and controlled using a sliding mode method. A modified Smith predictor is used to compensate time delays of the system. The control strategy is validated to be effective on the test bench. The comparison of energy consumption and operation point deviation between conventional speed regulation and the new method is presented.